Mechanism of the iron(II)-catalyzed hydrosilylation of ketones: activation of iron carboxylate precatalysts and reaction pathways of the active catalyst - Bleith, Tim Manuel; Gade, Lutz H. (Journal of the American Chemical Society, 2016)
A detailed mechanistic study of the catalytic hydrosilylation of ketones with the highly active and enantioselective iron(II) boxmi complexes as catalysts (up to >99% ee) was carried out to elucidate the pathways for precatalyst activation and the mechanism for the iron-catalyzed hydrosilylation. Carboxylate precatalysts were found to be activated by reduction of the carboxylate ligand to the corresponding alkoxide followed by entering the catalytic cycle for the iron-catalyzed hydrosilylation. An Eyring-type analysis of the temperature dependence of the enantiomeric ratio established a linear relationship of ln(S/R) and T-1, indicating a single selectivity-determining step over the whole temperature range from −40 to +65 °C (ΔΔG‡sel, 233 K = 9 ± 1 kJ/mol). The rate law as well as activation parameters for the rate-determining step were derived and complemented by a Hammett analysis, radical clock experiments, kinetic isotope effect (KIE) measurements (kH/kD = 3.0 ± 0.2), the isolation of the catalytically active alkoxide intermediate, and DFT-modeling of the whole reaction sequence. The proposed reaction mechanism is characterized by a rate-determining σ-bond metathesis of an alkoxide complex with the silane, subsequent coordination of the ketone to the iron hydride complex, and insertion of the ketone into the Fe-H bond to regenerate the alkoxide complex.
Gesehen am 13.05.2020